2010
DOI: 10.4049/jimmunol.0903065
|View full text |Cite
|
Sign up to set email alerts
|

Nod1 and Nod2 Are Expressed in Human and Murine Renal Tubular Epithelial Cells and Participate in Renal Ischemia Reperfusion Injury

Abstract: Nucleotide-binding oligomerization domain (Nod) 1 and Nod2 are members of a family of intracellular innate sensors that participate in innate immune responses to pathogens and molecules released during the course of tissue injury, including injury induced by ischemia. Ischemic injury to the kidney is characterized by renal tubular epithelial apoptosis and inflammation. Among the best studied intracellular innate immune receptors known to contribute to apoptosis and inflammation are Nod1 and Nod2. Our study com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 61 publications
1
88
0
1
Order By: Relevance
“…While these data have to be further investigated, they elicit the question concerning the role of Nod2 in other cell types than monocytes/macrophages, dendritic and epithelial cells. Indeed, Nod2 has been shown to be expressed in neutrophils [93], preadipocytes [94], osteoblasts [95], renal tubular epithelial cells [96],. .…”
Section: Discussionmentioning
confidence: 99%
“…While these data have to be further investigated, they elicit the question concerning the role of Nod2 in other cell types than monocytes/macrophages, dendritic and epithelial cells. Indeed, Nod2 has been shown to be expressed in neutrophils [93], preadipocytes [94], osteoblasts [95], renal tubular epithelial cells [96],. .…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous mice were intercrossed to generate homozygous Apoe 2/2 mice bearing combinations of Nod1 +/+ and Nod1 2/2 mice. The genotype for Apoe or Nod1 was confirmed using primers and conditions described in the The Jackson Laboratory Web site or the previous report (17), respectively. All mice were fed a normal chow diet and housed in a specific pathogen-free environment throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental studies have suggested that innate pattern recognition receptors may prime tissue and organ damage during ischemic states (Shigeoka et al, 2007(Shigeoka et al, , 2010Haneklaus et al, 2013). Testicular torsion is characterized by tissue damage and represents a urological emergency (Ringdahl and Teague, 2006), which, when misdiagnosed and inappropriately treated, can lead to male infertility (Antonuccio et al, 2006).…”
Section: Discussionmentioning
confidence: 99%